Misapprehension of mathematics among teachers, parents, and elementary school students - Khabibur Rohman; Turmudi Turmudi; Dasim Budimansyah; Ernawulan Syaodih (Intelektual Pustaka Media Utama, 2023)
Early mathematicians viewed mathematics as a beautiful and ethereal art form. However, the pupils in school appear to have no idea of this beauty. Misconceptions about mathematics among students, parents, and instructors are thought to be one of the root causes of the problem. Mathematical misconceptions and myths among instructors, parents, and students were examined in this study. These findings were obtained using a descriptive qualitative method of investigation. Research participants included elementary school pupils and their parents from East Java, Indonesia as well as 10 instructors, 10 students, and 10 parents. Random selection was used to pick the respondents. The results of this study showed that teachers, parents, and students have a wide range of misconceptions about mathematics. Among the misconceptions that occur among students, teachers and parents are: i) The conception of mathematics; ii) The aim of learning mathematics is only to train students to count and memorize formulas; iii) Mathematical ability is a genetic talent and only people who have talent will be proficient in mathematics; and iv) Mathematics is a non-applicable. The consequences of widespread misconceptions about mathematics among teachers, parents, and students are detrimental to the learning process and hinder the development of strong mathematical skills.